Trajetória da formulação e implantação da política habitacional de Belo Horizonte na gestão da Frente BH Popular: 1993 / 1996 - Monica Maria Cadaval Bede (2005)
This research aims to the rescue and analysis of the conception trajectory and implementation of the housing policy at the municipality of Belo Horizonte under the administration of the Peoples BH Front (Frente BH Popular), established by leftist parties and coordinated by Mayor Patrus Ananias, of the Labor Party. All dimensions and nuances of the housing policy of that period are approached and related to the most influential ideas and happenings that took place at the national and local contexts, which markedly interfered with the movements of municipalization and social mobilization in course throughout the country; with the trajectory and propositions of the peoples movements pleas for urban reform and housing and towards an innovative administration style, based on progressist municipal management experiences, implemented after the approval of the 1988 Federal Constitution. The Patrus Ananias administration faces the housing issue in a context of investment retraction by the Federal Government in the area, implying a continued adjustment of the actions in course, in order to cope with the context of resourcescarcity. Notwithstanding this scenery, andreflecting a behavioral characteristic of the municipal administrations at the time, the Belo Horizonte city hall significantly expands its own resource investment base and presents an outstanding quantitative performance as regards the implementation of a housing policy,under an intense process of formulation and execution of innovative intervention models. Effectively, this experience meant the redirection of the so far adopted managerial mode at the Minas Gerais capital, thus constituting a moment of transition between the conservative andthe progressist culture and practice, in tune with the conception of the urban reform movement and with the propositions of the housing movement. Internally, the main characteristics of this administration, as regards the housing issue, are the handling of opposing views, the permanent dialogue with the peoples movements and a significantpresence and contribution from external consultants.